Influence of oxygen on dielectric properties of HFO1336Mzz(E)/CO2 gas mixture - Rizwan, Ahmed; Rahisham, Abd Rahman; Muhammad Saufi, Kamarudin; Nor Akmal, Mohd Jamail; Md Nor Ramdon, Baharom; Amir Izzani, Mohamed; Ahsan, Mati Ullah (Institute of Electrical and Electronics Engineers Inc., 2023)
HFO1336Mzz(E) gas is regarded as a viable replacement gas for SF6 in gas-insulated equipment due to its superior insulating properties and low greenhouse gas potential (Global warming potential, GWP). This study analyses the power frequency breakdown characteristics, charge scattering, and insulation stability of HFO1336mzz(E) under the influence of O2 at different mixing levels. It is concluded that the addition of oxygen enhances the breakdown strength of the proposed gas mixture. The insulation strength of HFO1336Mzz(E) mixture with 2,4,6,8,10 % concentration increases the breakdown voltage by 5.35 %, 8.55%, 12.30%, 14.48%, and 15.10% respectively as compared to HFO1336Mzz(E)-CO2 mixture. The insulation stability of the gas mixture is improved with O2 addition up to 8 % above that level, and the stability is reduced. For engineering applications, 2-8% of O2 to the HFO1336Mzz(E)-CO2 gas combination is advised to enhance insulating performance.